Islam Indonesia : The Orientation of Islamic Studies and Contribution to Global Civilization - Ahmad Hifni; Syarifaeni Fahdiah; Nurul Infitah; Fathan Fihrisi (Dialogia: Islamic Studies and Social Journal, 2022)
The world increasingly recognizes Indonesia as the largest Muslim country, and as the third largest democracy after India and the United States. Indonesia is also known as a country with a washatiyah Islamic pattern, namely Islam that is in the middle, balanced, does not stand at the extreme pole, either in understanding or applying Islam. With this position and status, it is not surprising that many people hope that Indonesia can play a more prominent important role in the international arena. Expected roles include making scientific contributions, spreading Washatiyah Islam, and empowering democracy in the Muslim world. This paper aims to illustrate the importance of promoting Indonesian Islam to global civilization. The face of Indonesian Islam offers diversity in the spirit of togetherness. This research is the study of literature by reviewing the relevant literature. Indonesian Islam has different styles and responses to Islam that develop in other regions. This difference in Indonesian Islam occurs because a particular area has culture, customs, social construction, unlike other regions.